2008
DOI: 10.1007/s10750-008-9346-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of marine reserve protection on spiny lobster (Palinurus elephas Fabr., 1787) in a central western Mediterranean area

Abstract: The contribution that a small restocking area (central western Mediterranean) has made to the Palinurus elephas (Fabr., 1787) population was examined by comparing the abundances recorded inside and outside the area before (1997) and after the establishment of the reserve (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005). From 1998 to 2002 a progressive percentage increase of P. elephas biomass values was recorded both inside the area and in the surrounding zones. The total mean abundance within the reserve (CPU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…For example, Goñi et al (2001) showed that, depending on the season, densities of spiny lobster (Palinurus elephas) were 6-20 times greater within the Columbretes marine reserve (Spain) than in comparable fished areas. Similarly, Follesa et al (2008) found a progressive percentage increase of P. elephas biomass values both inside a re-stocking area in western Sardinia and in surrounding zones once the protection measures were implemented. This was also the case with the giant limpet (Patella ferruginea), once common in the Mediterranean, but which has been driven to near extinction, mostly by human collection (Laborel-Deguen & Laborel, 1991;Scotti & Chemello, 2000).…”
Section: Expected Ecological Effects At Population Levelmentioning
confidence: 76%
“…For example, Goñi et al (2001) showed that, depending on the season, densities of spiny lobster (Palinurus elephas) were 6-20 times greater within the Columbretes marine reserve (Spain) than in comparable fished areas. Similarly, Follesa et al (2008) found a progressive percentage increase of P. elephas biomass values both inside a re-stocking area in western Sardinia and in surrounding zones once the protection measures were implemented. This was also the case with the giant limpet (Patella ferruginea), once common in the Mediterranean, but which has been driven to near extinction, mostly by human collection (Laborel-Deguen & Laborel, 1991;Scotti & Chemello, 2000).…”
Section: Expected Ecological Effects At Population Levelmentioning
confidence: 76%
“…Follesa et al (2008Follesa et al ( , 2011 carried out studies on the spiny lobster in Su Pallosu based on experimental and commercial CPUE data and on recapture data of lobsters that were released inside the no-take zone after tagging. Su Pallosu is a 4 km 2 area located 6 km off the central-western coast of Sardinia (Italy).…”
Section: The Effects Of Mmas On Fisheriesmentioning
confidence: 99%
“…The study area comprises the Su Pallosu no‐take area (central western Mediterranean), created in 1997 to protect Palinurus elephas stocks and improve near‐by traditional fishing grounds. Studies, performed from 1998 to 2005 within the no‐take area to assess its effectiveness on the lobster population, showed that abundance within the reserve was 7.5 times greater than in the surrounding zones (Follesa et al ., ). Applying the Arnason Schwartz multistate mark recapture model (Arnason, ; Schwartz et al ., ) to 8 years of recaptured lobster data within and around the no‐take area (Follesa et al ., ) clearly indicated continuous movement of lobsters across the boundary of the no‐take area.…”
Section: Introductionmentioning
confidence: 99%